Two Nineteenth-Century Collectors-Curators Compared and Contrasted: General Augustus Henry Lane Fox Pitt-Rivers (1827–1900) and Augustus Wollaston Franks (1826–1897). Issue 2 (July 2014) - Petch, Alison
<x content-type="archive" xml:space="preserve">Abstract</x> The careers of General Pitt-Rivers and A. W. Franks, two of the leading collectors-curators of the nineteenth century, are compared and contrasted. A brief account of their lives is followed by accounts of their relationshship, collaborations, scholarly work, and collecting, as well as a discussion of their ideas about museum display and documentation. Comparing them in this way helps to put each man's career in perspective.